2018
DOI: 10.1080/19336918.2016.1243643
|View full text |Cite
|
Sign up to set email alerts
|

Augmented migration of mesenchymal stem cells correlates with the subsidiary CXCR4 variant

Abstract: Use of mesenchymal stem cells (MSCs) has been introduced as a promising tool, for structural and functional recovery of damaged tissues/organs. Studies have indicated that interactions between chemokine receptors and their ligands have a critical role in homing of MSCs to the site of injury. Although CXCR4 variants have been characterized, the exact role of each transcript in homing has remained unclear. In this study, cells were pretreated with various hypoxia-mimicking compounds (valproic acid, cobalt-chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(43 reference statements)
0
5
0
2
Order By: Relevance
“…In another study on a mesenchymal stem cell sheet, secretions of VEGF, bFGF and collagen I and III were enhanced under hypoxic conditions [ 39 ]. Along with an enhanced proliferation, the chemokine receptor (CXCR4) has also been demonstrated to be elevated on DPSCs under hypoxia [ 40 ]. The increased secretion of these pro-angiogenic and anti-inflammatory factors is what could provide a potential therapeutic application to DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on a mesenchymal stem cell sheet, secretions of VEGF, bFGF and collagen I and III were enhanced under hypoxic conditions [ 39 ]. Along with an enhanced proliferation, the chemokine receptor (CXCR4) has also been demonstrated to be elevated on DPSCs under hypoxia [ 40 ]. The increased secretion of these pro-angiogenic and anti-inflammatory factors is what could provide a potential therapeutic application to DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The most important role of Hypoxia-mimicking agents is considered as hypoxia-inducible factor-1a (HIF-1a) inducer, which becomes a critical regulator of the cellular reaction to hypoxia condition (Mirahmadi et al 2016b;Oses et al 2017;Woo et al 2006;Yoo et al 2016;). It was exhibited previously that in MSCs, hypoxia-mimicking agents boost stem cell migration by CXCR4/SDF-1 axis (Heirani-Tabasi et al 2018;Hung et al 2007;Tsai et al 2010). We hypothesized that these components may also prime Ad-MSCs for enhancement of homing by increasing migration-related signaling molecules.…”
Section: Introductionmentioning
confidence: 88%
“…Additionally, CXCR4 signaling increased in a dose-dependent manner, which seemed to be the result of increased hypermethylation of the CXCR4 gene promoter and chromatin remodeling. These results showed that VPA (2.5 mM for 3 months) might be involved in the differentiation of MSCs into hepatic cells through various mechanisms [ 115 , 116 ]. Moreover, exposure of MSCs obtained from elderly donors to specific concentrations of VPA increased their immortality by specifically activating the CXCR4 signaling pathway [ 117 ].…”
Section: The Effect Of Asms On Mscsmentioning
confidence: 99%